Analysis of working posture and risk of musculoskeletal complaints among vegetable farmers - Ni Luh Putu Chandra Dewi; Gede Parta Kinandana; Ni Luh Putu Gita Karunia Saraswati; Ni Komang Ayu Juni Antari (Physical Therapy Journal of Indonesia, 2024)
Background: Musculoskeletal disorders (MSDs) are disorders of body tissue that are related to movement, such as muscles, tendons, ligaments, nerves, or spinal joints. Farmers often experience these musculoskeletal complaints. This study aims to determine the risk level of working postures, the distribution of musculoskeletal complaints, and the risk level of musculoskeletal complaints among vegetable farmers. Methods: The research method used is descriptive observational. The sampling technique used was total sampling. The number of samples obtained in this research was 147 samples. Data collection was conducted at Banjar Taman Tanda, Batunya Village, Baturiti District, Tabanan Regency. Data collection was carried out by measuring work posture with rapid entire body assessment (REBA) and measuring musculoskeletal complaints with a Nordic body map (NBM). The data analysis technique in this research is univariate analysis, namely age, gender, smoking habits, work duration, work period, work posture, and musculoskeletal complaints. Results: The research results showed that the majority of respondents had a risk level of work posture. The majority of respondents were classified as a medium risk level, 90 people (61.2%), a low-risk level, 24 people (16.3%), a high-risk level, 30 people (20.4%). %), and the risk level is very high, with the minimum number of people being three people (2.0%). The results of measuring the level of musculoskeletal complaints with NBM found that the majority of complaints were not painful in the right elbow of the body, as many as 120 people (81.6%), the majority of complaints of slight pain were in the right leg, 51 people (34.7%), the majority of complaints of pain were in. The right shoulder of the body was 43 people (29.3%), and the majority of complaints of severe pain were in the waist, 58 people (39.5%). The highest risk level for musculoskeletal complaints was at a moderate risk level, 84 people (56.5%). Conclusion: There were differences in the risk level of musculoskeletal complaints and work posture among vegetable farmers.